Risk Assessment of Inhalation Exposure to the Use of Chemicals in the Mineral Processing - Susanto, Arif; Mauliku, Novie Elvinawaty; Suhat, Suhat; Nugrahaeni, Dyan Kunthi; Budiana, Teguh Akbar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Chemical exposure known as chemical hazards and toxic substances (CHTS), which occur through inhalation, ingestion, and skin contact, causes serious illness, irritation, corrosion, injury, and even death. The chemicals analyzed are limited to the reagents used in the mineral ore production process, in addition to dermal exposure. Data on hazard identification and exposure evaluation were collected. The utilization of CHTS will continue to increase in the coming years, thereby leading to health impacts on workers. Global data released by ILO showed a 270 million (62.8%) and 160 million (37.2%) rise in work accidents and illnesses, culminating in 430 million per year. Data on the number of workers who received benefits from the Work Accident Insurance program of the National Social Security Agency for Employment (known as BPJSTK), showed that 210,789 people (4,007 fatal) 221,740 people (3,410 fatal), and 234,370 people (6,552 fatal) experienced work-related accidents and illnesses in Indonesia. Therefore, this qualitative study aims to examine and analyze the health risks of mining workers exposed to CHTS through inhalation- using the observation method. The Chemical Health Risk Assessment (CHRA) method issued by the Malaysian Department of Safety and Health in 2018 was used to assess the inhalation exposure rate. The analyzed chemicals were limited to reagents used in production with data collected through the semi-quantitative method. The results showed that the inhalation exposure risk level is categorized as moderate and capable of causing health defects related to acute toxicity and specific target organ toxicity-single exposure (STOT-SE). Furthermore, 4 (four) out of 6 (six) reagents were identified as having significant inhalation exposure risk, hence, controls related to Occupational Health and Safety (OHS) in the mineral ore processing process must be increased.